Global Modeling of the Inner Magnetosphere Under the Influence of a Magnetic Cloud Associated With an Interplanetary Coronal Mass Ejection: Energy Conversion and Ultra‐Low Frequency Wave Activity. Issue 10 (27th October 2022) - Jauer, P. R.; Wang, C.; Echer, E.; Souza, V. M.; Da Silva, L. A.; Marchezi, J. P.; Alves, L. R.; Alves, M. V.; Douglas, S.; Loesch, C.; Liu, Z.; Hui, L.; et al.
Abstract: The interaction and response of the magnetic cloud‐type structure with Earth's magnetosphere were modeled by the SWMF/BATS‐R‐US code. The conversion of magnetic ( E m ), kinetic ( E k ), and internal ( E i ) energies was analyzed as well as the wave power integrated in the ultra‐low frequency (ULF) range of the poloidal ( E ϕ ) and toroidal ( E r ) electric field components in the equatorial region of the magnetosphere, in seven 2‐hr long intervals, namely, I 1 through I 7. The intensity of energy conversion and wave activity for I 1 and I 7 intervals was negligible. The energy conversion started in the I 2 interval and extended to the I 3, I 4, and I 5 intervals. The power of the E ϕ and E r components in the dayside and nightside regions is clearly observed. The I 4 corresponds to interplanetary magnetic field (IMF) B z mostly southward and the I 5 has similar amplitudes of the B z and B y components, corresponding to the period of the high geomagnetic activity. The conversion rate for the I 4 and I 5 was similar, however, the integrated power spectral density (IPSD) of the E ϕ and E r components is more intense in I 5. During the I 6 interval, with predominant IMF B y, the energy conversion rate is intensified mostly for inner radial distances R < 6 R E, and the E k component becomes close to zero for outer regions. The energy conversion regions are located spatially close to or overlapping with regions where the IPSD in the ULF range is intensified. The energy conversion in the inner magnetosphere occurred preferentially between E m and E i, with the E k energy component always present but with lower intensities. Key Points: Energy conversion is always present in the equatorial region near to or overlapping with places where there is ultra‐low frequency (ULF) wave intensification Energy conversion occurs predominantly between magnetic and internal energies with a smaller contribution of the kinetic energy term Higher dynamic pressure significantly increases energy conversion rate and ULF wave activity in both dayside and nightside magnetosphere